Can Spousal Sexual Assault Cases be Detected without any Psychiatric Findings? - Karbeyaz, Kenan; Çelikel, Adnan; Ortanca, ibrahim (The Bulletin of Legal Medicine, 2017)
Objective: Whether spousal rape is a misconduct or not has been a controversial topic for a long time in the jurisdictional system of our country. Sexual assault against one’s spouse has been declared as a criminal act by the change in the Turkish Criminal Code on 1st June 2005. However, we think that psychiatric evaluation of the victim has been ignored by the change in the related penal code in 2014. In this study our aim is to evaluate sexual assaults in marriage and understand and present the importance of psychological findings. Materials and Methods: Data of the sexual assault cases by one’s spouse during the six years period between 2011 and 2016 who were evaluated by Eskişehir Office of Council of Forensic Medicine were analyzed with their psychiatric evaluation findings. Results: In 6 years 27 spousal rape victims were evaluated. Among them, 48.2 % were in the 17 to 24 years’ age group. Only two (7.4 %) had a university degree. Only one case was evaluated after the Turkish Criminal Code has changed. In only 9 (%33.3) cases, findings of the assault were observed by physical and genital examination. By psychiatric evaluation, psychiatric findings related to sexual assault has been determined in all cases. It is determined that without psychiatric evaluation, in the two third of cases no evidence would be obtained and therefore no prosecution could be conducted. Conclusion: Without psychological findings, the sexual assault evaluation is incomplete. Therefore, the related article of penal code needs regulation. The psychiatric findings should be considered as evidence in sexual assault cases and this must be clearly defined in the Criminal Code. Units both for children and adolescents should be established in all cities immediately, in which the psychiatrists and forensic medicine specialists could work together.